Strategy for Independence and Economic Empowerment Using SWOT Analysis: A Case Study of Islamic Boarding Schools in North Sumatra - Elaeis Guineensis Jalil HSB; Muhammad Syukri Albani Nasution; Rahmi Syahriza (Faculty of Islamic Business and Management, 2026)
Islamic boarding schools (pesantren) have become a significant economic force in many regions in Indonesia. However, Islamic boarding schools often face challenges in terms of capital, management, market access, and infrastructure, making it difficult to maximize independence. Furthermore, the Islamic boarding school independence program is a strategic agenda mandated by Law Number 18 of 2019. Therefore, this research aims to develop strategies for independence and economic empowerment of Islamic boarding schools. This research is qualitative and inductive. The research location is an Islamic boarding school in North Sumatra. The data analysis used is a SWOT analysis. The results of the SWOT analysis indicate that Islamic boarding schools are positioned in an SO (Strength-Opportunities) strategy, a strategy that emphasizes utilizing internal strengths to seize and optimize available opportunities in developing Islamic boarding school businesses.Keywords: Independence, Empowerment, Islamic Boarding Schools, SWOT.